Electrocatalytic hydrogen evolution reaction with a supramolecular cobalt(II)phthalocyanine carrying four cobaloxime moieties - KOCA, ATIF (ELSEVIER SCIENCE SA, 2017)
A supramolecular cobalt phthalocyanine (CoPc) bearing four redox active cobaloxime (CoDMG) substituents ((CoDMG)(4)-CoPc) was synthesized and electrochemically characterized in order to determine its functionalities for practical usages as effective electrocatalysts. Voltammetric analyses of CoDMG, CoPc, and (CoDMG)(4)-CoPc indicated redox activity of each compounds and supported substitution of CoPc with CoDMG. (CoDMG)(4)-CoPc showed three CoPc based reduction processes and two CoDMG based reduction processes. While CoDMG showed two reduction and one oxidation processes, CoPc illustrated three reduction and two oxidation processes. Binding of CoDMG to CoPc increased the reduction processes to five. Multi-electron and metal and/or ring based redox processes showed worthy of the (CoDMG)(4)-CoPc for using as an electrocatalyst. Shifting of the proton reduction reaction toward the positive potentials indicated electrocatalytic activities of the complexes for the hydrogen evolution reaction (HER). Among CoDMG, CoPc, and (CoDMG)(4)-CoPc, modified glassy carbon electrode with (CoDMG)(4)-CoPc illustrated the highest electrocatalytic activity and it decreased the over-potential of the bare electrode about 360 mV and increased the current density of the electrode about 10-fold. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Supramolecule; Electrocatalyst; Hydrogen evolution reaction; Phthalocyanine; METAL-FREE; PHTHALOCYANINES; COBALT; ELECTRODES; COMPLEXES; WATER; SPECTROELECTROCHEMISTRY; METALLOPORPHYRIN; DERIVATIVES; REDUCTION